Errors in Indonesian-English Consecutive Interpreting: A Case Study in Interpreting Class Practice - Ni Wayan Swardhani Wiraswastiningrum (Jurnal Linguistik Terapan, 2024)
This study explores consecutive interpretation, which involves listening, note-taking, and reproducing speech and can lead to errors similar to those in spoken language production. Previous research has investigated various strategies and error types in consecutive interpretation, highlighting the challenges faced by novice interpreters and the factors that affect speech errors, including language proficiency, working memory, and anxiety. Focusing on interpreting practice recordings conducted in class on health topics, the study aims to examine the types of errors and issues identified in the case study. The study utilizes error parameters established by Gonzalez et al. (1996), Barik (1998), Hairuo (2015), Chinh (2010), and Altman (1994). This qualitative study follows a systematic approach to data collection, employing recordings from the observation phase. Two distinct data sets were generated: from English to Bahasa Indonesia (BA) and the reverse interpretation from Bahasa Indonesia to English (AB). A total of 64 data points were collected, comprising 52 from the BA set and 12 from the AB set. Transcriptions were completed for both sets, and the resultant data were categorized according to the aforementioned error parameters. This study identifies six types of errors in the analyzed object, of which five fall under the stated error parameters. Meanwhile, the sixth was identified explicitly within the context of this study. The reasons for these errors vary, ranging from the interpreter's lack of experience and competence to intentional attempts to deliver a more natural interpretation and clarify the intended message.